PENGARUH TAX PLANNING, INVESTMENT OPPORTUNITY SET DAN FREE CASH FLOW TERHADAP MANAJEMEN LABA - Putri Nabilah (JEKOS (Jurnal Ekonomi Dan Sosial), 2026)
This study aims to analyze the effect of Tax Planning, Investment opportunity set, and Free cash flow on Profit Management. The type of research is quantitative with an associative approach. The research population is companies in the Basic Materials Sector listed on the Indonesia Stock Exchange (IDX) during the period of 2019 – 2023. The sample withdrawal technique used is the Purposive Sampling Technique. Hypothesis testing uses panel data regression with the help of the eviews statistical tool 13. The results of the study show that Tax planninghave an influence on Profit Management while Investment opportunity set and Free cash flow has no influence on Profit Management. In terms of Investment opportunity set and Free cash flow have an influence on Profit Management.   Keywords : Tax Planning; Investment opportunity set; Free cash flow; Profit Management